A first record of the antioxidant defense and selected trace elements in Salamandra salamandra larvae on Mt. Avala and Mt. Vršački Breg (Serbia) - Pavlović, Slađan; Krizmanić, Imre; Borković-Mitić, Slavica; Stojsavljević, Aleksandar; Mitić, Bojan (Archives of Biological Sciences, 2020)
Paper description: The antioxidant defense system and concentrations of selected trace elements in the fire salamander (Salamandra salamandra) larvae from Mt. Avala and Mt. Vršački Breg, Serbia, were examined. Salamander larvae from Mt. Vršački Breg had lower weights and lengths than larvae from Mt. Avala. Antioxidant enzyme activities were higher, while the content of sulfhydryl groups was lower in larvae from Mt. Vršački Breg than in those from Mt. Avala. There were no correlations between the concentrations of trace elements in water and animal tissue. The reported changes are the result of developmental differences and habitat characteristics. Abstract: We investigated the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione reductase (GR) and the phase II biotransformation enzyme glutathione S-transferase (GST) in the whole body of fire salamander larvae (Salamandra salamandra) from two localities on Mt. Avala (AVS and ABP) and one locality on Mt. Vršački Breg (VSB), Serbia. We also determined the total glutathione (GSH) and sulfhydryl group (SH) contents, as well as the concentrations of manganese (Mn), copper (Cu), zinc (Zn), selenium (Se), arsenic (As), cadmium (Cd), lead (Pb) and uranium (U). The obtained results show that animals from VSB had significantly lower weights and lengths than animals from AVS and ABP. The activities of all investigated enzymes were significantly higher, while the SH content was significantly lower in animals from VSB compared to those from AVS and ABP. No correlations between trace-element concentrations in water and animal tissue were observed. We concluded that the obtained results were more likely a consequence of the combination of developmental differences and the effects of different habitat conditions, environmental and anthropogenic influences than of concentrations of trace elements in the water alone.